THE EFFECT OF USING LOCAL LANGUAGE ON STUDENT PRESENTATION SKILLS - Winda Puspita; Windi Natalia; Fikri Hakim (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
This research aims to describe the effect of using regional languages ​​on students' presentation skills and is a study or semantic rules. This research uses a qualitative-descriptive method which describes all elements related to the research objectives and literature methods. This research data is the effect of using regional languages ​​on students' presentation skills. The data sources are books, journals, scientific articles which can be accessed on Google Scholar, and Siliwangi University students. Some data is also taken or referred to from internet sources and interview techniques. Data was collected using reading methods and note-taking techniques. Data analysis is carried out qualitatively and interpreted by reviewing all the data collected, then carrying out data reduction and classification and finally presenting the results.